Energy and Emissions : Local and Global Effects of the Rise of China and India - Shalizi, Zmarak (World Bank, Washington, DC, 2012)
Part 1 of the paper reviews recent trends in fossil fuel use and associated externalities. It also argues that the recent run-up in international oil prices reflects growing concerns about supply constraints associated with declining spare capacity in OPEC, refining bottlenecks, and geopolitical uncertainties rather than growing incremental use of oil by China and India. Part 2 compares two business as usual scenarios with a set of alternate scenarios based on policy interventions on the demand for or supply of energy and different assumptions about rigidities in domestic and international energy markets. The results suggest that energy externalities are likely to worsen significantly if there is no shift in China's and India's energy strategies. High energy demand from China and India could constrain some developing countries' growth through higher prices on international energy markets, but for others the "growth retarding" effects of higher energy prices are partially or fully offset by the "growth stimulating" effects of the larger markets in China and India. Given that there are many inefficiencies in the energy system in both China and India, there is an opportunity to reduce energy growth without adversely affecting GDP growth. The cost of a decarbonizing energy strategy will be higher for China and India than a fossil fuel-based strategy, but the net present value of delaying the shift will be higher than acting now. The less fossil fuel dependent alternative strategies provide additional dividends in terms of energy security.